Interpersonal Communication of Madrasah Heads in Increasing Teacher Work Motivation - Khasanah Ilmi (Business and Applied Management Journal, 2024)
The purpose of this study was to determine the role of interpersonal communication of the principal in improving teacher work motivation in madrasahs. This study is based on the importance of interpersonal communication of the principal in motivating teachers. The type of research in this study is descriptive qualitative research. The informants of this study are key informants and supporting informants. Data collection techniques use observation, interview and documentation techniques. Data analysis techniques use data reduction, data presentation and data verification. The findings of the study indicate that the participatory leadership style of the madrasah principal significantly increases teacher motivation and involvement in the learning process. The application of effective interpersonal communication strategies, including openness, empathy, and support, contributes to the creation of mutual trust and a harmonious work environment. Although there are inhibiting factors such as lack of resources and administrative support, the existence of supporting factors such as clear communication and a positive school culture increases teacher work motivation. This study is expected to contribute to the understanding of the factors that influence teacher motivation and performance in educational institutions through leadership.